2018
DOI: 10.1017/s0305000918000399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how time flies and what it means to be on cloud nine: English as an Additional Language (EAL) learners’ metaphor comprehension

Abstract: We explored the vocabulary and metaphor comprehension of learners of English as an additional language (EAL) in the first two years of UK primary school. EAL vocabulary knowledge is believed to be a crucial predictor of (reading) comprehension and educational attainment (Murphy, 2018). The vocabulary of five- to seven-year-old children with EAL was compared to that of English monolinguals (N = 80). Comprehension was assessed for both verbal (e.g., time flies) and nominal metaphors (be on cloud nine) of varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Since EAL children's English proficiency is highly predictive of their educational success and personal well-being (Strand & Demie, 2005;Strand & Hessel, 2018;Whiteside, Gooch, & Norbury, 2017), it is important to understand these challenges. EAL learners often lag behind monolinguals in reading comprehension and this is linked to relative deficits in vocabulary size and depth, but not reading fluency (Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;D'Angiulli, Siegel, & Serra, 2001;Hessel & Murphy, 2019;Lesaux, Rupp, & Siegel, 2007;Spätgens & Schoonen, 2018;Spencer & Wagner, 2017;Verhoeven, 2000). There is some evidence that EAL learners are less adept at comprehension monitoring, that is, with checking and regulating their understanding when reading figurative and multi-word phrases (Burgoyne, Whiteley, & Hutchinson, 2013;Kan & Murphy, in press).…”
Section: Comprehension Monitoring During Reading: An Eye-tracking Study With Children Learning English As An Additional Languagementioning
confidence: 99%
“…Since EAL children's English proficiency is highly predictive of their educational success and personal well-being (Strand & Demie, 2005;Strand & Hessel, 2018;Whiteside, Gooch, & Norbury, 2017), it is important to understand these challenges. EAL learners often lag behind monolinguals in reading comprehension and this is linked to relative deficits in vocabulary size and depth, but not reading fluency (Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;D'Angiulli, Siegel, & Serra, 2001;Hessel & Murphy, 2019;Lesaux, Rupp, & Siegel, 2007;Spätgens & Schoonen, 2018;Spencer & Wagner, 2017;Verhoeven, 2000). There is some evidence that EAL learners are less adept at comprehension monitoring, that is, with checking and regulating their understanding when reading figurative and multi-word phrases (Burgoyne, Whiteley, & Hutchinson, 2013;Kan & Murphy, in press).…”
Section: Comprehension Monitoring During Reading: An Eye-tracking Study With Children Learning English As An Additional Languagementioning
confidence: 99%
“…Research on reading skills with EAL children (i.e., minority language children in English-speaking contexts) has consistently demonstrated that EAL children tend to have matched, or sometimes even superior skills in decoding, yet often have problems with reading comprehension. In other words, they have good single word reading accuracy but struggle to extract meaning from text, likely due to smaller English vocabulary (e.g., Bialystok, Luk, Peets, & Yang, 2010;Burgoyne, Kelly, Whiteley, & Spooner, 2009;Cameron, 2002;Hessel & Murphy, 2018;Hutchinson, Whiteley, Smith, & Connors, 2003;Mahon & Crutchley, 2006;Pearson, Fernandez, & Oller, 1993;Smith & Murphy, 2015).…”
Section: Reading Comprehension In Students With Ealmentioning
confidence: 99%
“…A Language Background Questionnaire (LBQ), adapted from Beech and Keys (1997), was used to confirm language group status. This adapted LBQ has been used in a number of our studies (e.g., Hessel & Murphy, 2018;McKendry & Murphy, 2011;Smith & Murphy, 2015) and has been a reliable index of children's EAL status in the absence of administering an independent, objective measure of their home language proficiency. This would of course be the ideal but given the significant linguistic diversity in the EAL population in England, developing, finding and/or implementing tests of home language proficiency remains a serious challenge.…”
Section: Instrumentsmentioning
confidence: 99%
“…Since EAL children's English proficiency is highly predictive of their educational success and personal well-being (Strand & Demie, 2005;Strand & Hessel, 2018;Whiteside, Gooch, & Norbury, 2017), it is important to understand these challenges. EAL learners often lag behind monolinguals in reading comprehension and this is linked to relative deficits in vocabulary size and depth, but not reading fluency (Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;D'Angiulli, Siegel, & Serra, 2001;Hessel & Murphy, 2019;Lesaux, Rupp, & Siegel, 2007;Spätgens & Schoonen, 2018;Spencer & Wagner, 2017;Verhoeven, 2000). There is some evidence that EAL learners are less adept at comprehension monitoring, that is, with checking and regulating their understanding when reading figurative and multi-word phrases (Burgoyne, Whiteley, & Hutchinson, 2013;Kan & Murphy, in press).…”
Section: Comprehension Monitoring During Reading: An Eye-tracking Stumentioning
confidence: 99%